Coyuntura Económica - Rozo, María Carolina; Martínez Sandoval, Avelino; Vela Enríquez, Luz Amelia; Sánchez, Holmes; Aponte, Guillermo (Revista de Economía & Administración E-ISSN 2463-1035 ISSN 1794-7561, 2009)
Coyuntura económica